The Formulation Cream Of Black Cumin Seed Oil (Nigella sativa Linn.) - Utami, Dinda Sari; Lubis, Minda Sari; Meilani, Debi (Pustaka Media Publishing, 2023)
Indonesia is rich in natural resources, has done a lot of research on the utilization of natural materials. Nigella sativa Linn. or in Indonesia known black jintan has pain relieving or analgesic and anti-inflammatory properties. The aim of this study is to determine the antinyeri effect of black ginger oil on white male rats by plantar test method. Black ginger seed oil is standardized and performed test effectiveness, then black gender oil is made cream with concentrations of 5ml, 10ml, and 20ml. Observations were performed for the occurrence of muscle antinyeri every 15 minutes during the time the plantar test device stopped when the mice licked their legs and hands.The test results of the standardization of black geranium seed oil obtained type weight in black germanium oil 0.958 g/ml, water content 0.000056%, and acid count 39.97 ml/g. Physical quality test results the preparation of the cream no bruising with the oil emulsion type in water that is easily washed with water as well as pH adjusted with the skin with range 7.3-7.6 and the cream does not undergo color change, shape and rupture emulsions.